Anti-Nutritional Factors and Potassium Bromate Content in Bread and Flour Samples in Uyo Metropolis, Nigeria - A. S. Ekop; I. B. Obot; E. N. Ikpatt (E-Journal of Chemistry)
The aim of the study is to evaluate the anti-nutritional composition factors and potassium bromate content of some selected bread and flour samples in Uyo Metropolis. The result of the analysis shows that, though the concentration of phytic acid and tannins was high in both the bread and flour samples their concentrations did not exceed lethal doses. The potassium bromate content was minimal in all the bread and flour samples and within safe limits of residual bromide found in flour as specified by the US Food and Drug Administration. The concentrations of the anti-nutritional factors in the bread and flour samples were partially different from each other when subjected to the students t-test statistics.